Pioneering e-FAST in North Macedonia: A Resource-Efficient Approach to Polytrauma Care (Prospective Cohort Study) - Brzanov, Nikola; Gavrilovska Brzanov, Aleksandra; Kuzmanovska, Biljana; Jovanovski Srčeva, Marija; Trpeski, Simon; Antović, Svetozar; Nastasović, Tijana (Scripta Medica, 2025)
Background/Aim: Polytrauma is a leading cause of morbidity and mortality worldwide, particularly in low- and middle-income countries with limited healthcare resources. The "golden hour" following trauma is critical for effective intervention, yet reliance on computed tomography (CT) for diagnosis often delays treatment due to logistical challenges. Focused assessment with sonography for trauma (FAST) has emerged as a rapid, bedside diagnostic tool, offering a potential solution in resource-limited settings. This study evaluates the utility of FAST in the management of polytrauma patients in North Macedonia, focusing on its impact on diagnostic efficiency, patient outcomes and resource allocation.Methods: A prospective longitudinal randomised clinical trial was conducted on 80 polytrauma patients, divided into two groups: one receiving FAST followed by CT (FAST/CT) and the other undergoing CT alone. Diagnostic time, accuracy, surgical intervention rates, hospitalisation duration and mortality were compared between the groups. Statistical analysis was performed using descriptive and analytical methods.Results: A total of 80 polytrauma patients were included and randomly assigned to a FAST/CT group or a CT-only group. FAST significantly reduced diagnostic time compared with CT alone (mean 5.12 vs 23.55 minutes), without delaying subsequent CT imaging or definitive diagnosis. Both FAST and CT demonstrated high accuracy in detecting thoracic (92.5 % vs 97.5 %) and abdominal injuries (85 % vs 86.25 %), with a 97.5 % agreement between methods. No significant differences were observed between groups regarding surgical intervention rates, length of hospital stay, or mortality. Conclusion: FAST proved to be a cost-effective, non-invasive and efficient diagnostic tool, particularly valuable in resource-limited settings. While its limitations, including false negatives, necessitate complementary CT for stable patients, FAST optimises trauma care by streamlining diagnosis and resource allocation. Challenges such as equipment availability and operator training must be addressed for effective implementation.